Virtual Laboratories on Student Engagement: A Systematic Review of Inquiry-Based and Problem-Based Learning Effectiveness - Faresta, Rangga Alif; Ginola, David; Sinambela, Indah Astri Natalia; Apriliana, Apriliana (UNDIKMA, 2025)
This literature review aims to investigate the impact of virtual labs integrated with Inquiry-Based Learning (IBL) and Problem-Based Learning (PBL) models on student engagement in Science and Physics education. The review examines the effectiveness of applying IBL and PBL models through a systematic literature review, using the PRISMA framework as the protocol. The selected database for this study is SCOPUS, covering the period from 2018 to 2024. The initial screening yielded 1359 articles, of which 20 met the eligibility criteria. This study highlights the paper distribution regarding the virtual laboratories integrating with IBL and PBL showing a positive trend that indicates the field of study has potential for further exploration. Moreover, the study revealed the positive impact on student engagement both from IBL and PBL assisted by Virtual Laboratories.Â